TREATMENT OUTCOMES AND SOME FACTORS RELATED TO COAGULATION DISORDERS IN NEONATES WITH SEPTICIA AT HAI PHONG PEDIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate treatment outcomes and describe some factors associated with coagulation disorders in neonates with sepsis.Subjects and methods: A case series study was conducted on 32 neonates with culture-proven sepsis from August 2023 to September 2025.Results: A total of 71.9% of neonates were successfully treated and discharged from the hospital while 5 cases (15.6%) resulted in death. The mean duration of treatment was approximately 25.8 ± 17.7 days (primarily 7-28 days). Preterms had a 10.5-fold higher risk of coagulation disorders compared to term infants. Anemic neonates had a 13-fold higher risk, and those presenting with bleeding manifestations had a 7-fold higher risk of coagulation disorders.Conclusion: The mortality rate among neonates with sepsis was 15.6%. Prematurity, anemia, and bleeding manifestations were identified as risk factors for coagulation disorders.
Keywords: Coagulation disorders, neonatal sepsis, Hai Phong Pediatric Hospital.